SECONDARY STUDENTS' ENGAGEMENT IN TASK-BASED LANGUAGE TEACHING IN READING CLASSROOM - Arnisa Salsabella; Indah Purnama Dewi (IKIP Siliwangi, 2022)
Reading is one of essensial skills in learning English. Students need to be good especially in reading comprehension to measure students’ comprehension on passage. Some previous studies stated that reading comprehension can be help by using Task-Based Language Teaching method to see students’ engagement. However, there is no study that involving students’ engagement, that is can be helped students to be more active in reading classroom. Therefore, this article tries to explain students’ engagement in Task-Based Language Teaching in reading classroom. This article is using qualitative method with descriptive case study, this article describes through observation checklis, semi-structured interview, and documentation. The results show that students needed to be pushed by the teacher, the students also did not know about TBLT before the teacher explained to them but from the interview most of them said that TBLT is an interesting method, it really did not effect the students in reading comprehension. It is because several factors such as less influence about TBLT method, less knowledge about reading comprehension, and less interest in reading english text. Keywords: Students’ Engagement, TBLT, Reading Comprehension